Motion Equations Isotropic and Orthotropic Plate Impacted by Elastic Rod - Soukup, J.; Skočilas, J.; Skočilasová, B.; Ryhlíková, L. (Journal of Applied Nonlinear Dynamics, 2026)
The article deals with solution of the motion equations of plate. The rectangular plate is loaded by elastic rod which influences rectangular plate with force. The direction of the force is perpendicular to the face upper surface of the rectangular plate. The solution is derived for isotropic and orthotropic material. The solution of the motion equations has no analytical solution. The new approximation of the solution based on the transformation of integral equations to system of algebraic equations is presented.